2022
DOI: 10.2147/idr.s370967
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Aspergillosis in Cancer Patients in Taiwan

Abstract: Purpose The incidence of aspergillosis is increasing, and the risk factors for infection include cancer, admission to the intensive care unit, chronic pulmonary diseases, immunocompromised status, and taking immunomodulatory drugs. There are limited data about the incidence of aspergillosis in patients with different types of cancer. The aim of our study was to survey the incidence of aspergillosis in different cancer types from 2006 to 2017. Patients and Methods Data w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…A recent review article and case report also emphasized that immunotherapy may induce infection complications due to dysregulated immunity. 15,16 The European Society of Clinical Microbiology and Infectious Diseases proposed a consensus statement that immunosuppressive therapy to treat immune-related adverse events contributes to the risk of opportunistic infections compared to using ICIs alone. 22 In our study, there was only a nonsignificant trend in increasing IPA risk with steroid use.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A recent review article and case report also emphasized that immunotherapy may induce infection complications due to dysregulated immunity. 15,16 The European Society of Clinical Microbiology and Infectious Diseases proposed a consensus statement that immunosuppressive therapy to treat immune-related adverse events contributes to the risk of opportunistic infections compared to using ICIs alone. 22 In our study, there was only a nonsignificant trend in increasing IPA risk with steroid use.…”
Section: Discussionmentioning
confidence: 99%
“…They found that 16 of 1200 (1.6%) patients met the CPA diagnosis criteria. 21 Chen et al 15 showed that the incidence rate of pulmonary aspergillosis among male and female patients with all stages of lung cancer was 12.52 and 7.53 per 10,000 person-years, respectively. In our study, the prevalence may be underestimated since only 290 of 2543 advanced lung cancer patients received GM testing.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are very limited data available about the incidence of aspergillosis in patients suffering from cancer. However, an increasing trend of aspergillosis has been observed in cancer patients (Chien et al 2022) [26]. Sometimes, the invasive pulmonary aspergillosis (IPA) is found mimicking as the metastatic lung cancer (Michiel et al 2018) [27].…”
Section: Allergic Aspergillosis Including Abpa Sinus and Ear Canal In...mentioning
confidence: 99%